Clinical Characteristic of Covid-19 Infection in Pediatric: A Systematic Review - Annisa Istiqamah Ahmad1, Tri Setiawaty2, Rosmala Nur3, Rahman Kadir4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
SARS-CoV-2 is a new type of corona virus that has been identified as a cause of COVID-19 cases. Thisdisease is transmitted quickly, causes a global pandemic and can affect all ages, including children. Inchildren, cases are still rare and hard to be found. Because the prevalence of events in children tends to besmaller than in adults, information about the clinical characteristics of COVID-19 infection in children isstill lacking. The aim of this research is to find out the clinical characteristics of COVID-19 infections inchildren. Conducting a literature review of various scientific studies related to the clinical characteristicsof COVID-19 infection in children. The most common clinical symptoms found in pediatric patients withCOVID-19 infection are coughing, fever and gastrointestinal symptoms where these symptoms usuallytend to be mild to moderate and often the symptoms are not specific or asymptomatic. Laboratory resultsare generally normal but the CT-Scan results show suspicion towards pneumonia in the majority cases ofchildren.